PHYTOCHEMICAL CHARACTERIZATION, IN VITRO AND IN SILICO STUDIES ON THERAPEUTIC POTENTIAL OF EDIBLE AND WILD MUSHROOMS - S, JEYA PREETHI; SHARMILA P; SANGEETHA K; PONMURUGAN P (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The present study evaluates the in vitro and in silico analyses of mushrooms such as Agaricus bisporus, Pleurotus ostreatus, Ganoderma wiiroense, and Pleurotus tuber-regium. Methods: The quantitative and qualitative analysis of the mushrooms was analyzed and their antioxidant, antimicrobial, and anti-inflammatory assays were done. In addition, molecular docking of their bioactive compounds was docked against the targeted proteins. Results: The study found that the ethanolic extract of P. ostreatus contained high amounts of carbohydrates, phenolics, and flavonoids. The hot water extract of A. bisporus showed antioxidant activity in phosphomolybdenum assay, while G. wiiroense showed the highest antioxidant activity in superoxide radical scavenging assay. The ethanol extract of the latter also showed maximum 2,2-Diphenyl-picrylhydrazyl radical scavenging and ferric-reducing antioxidant power (reducing activity). A. bisporus hot water extract showed the highest inhibitory activity against Escherichia coli, while G. wiiroense showed the highest anti-inflammatory activity. In silico analysis revealed that chlorogenic and ganodermic acids had high binding affinity toward protein targets. Conclusion: The study compared the biological activities of commercial edible and wild mushrooms extracts, finding that active compounds from both mushrooms were effective against diseases such as cancer, tuberculosis, and rheumatoid arthritis through computational approaches